A Tradução Intersemiótica na construção da personagem Holly Golithly em Breakfast at Tiffany’s: entre o romance e o cinema - Branco, Sinara de Oliveira; Maciel, Mariana Assis (Revista da Anpoll, 2018)
The purpose of this text is to analyze the intersemiotic construction of Holly Golithly in two contexts: the novel and the film Breakfast at Tiffany’s (1961). Along the film adaptation, the focus will be on the observation of how people and places influence her behaviour, taking into consideration the relationship between the imagetic and the verbal contexts (word-image relationship). The theoretical framework used is based on the Theory of Adaptation; the Intersemiotic Translation; Subtitling; Image Analysis and Film Narrative. The multimodal corpus compiled involves the selected scenes from the film, offering frames and subtitles, as well as excerpts from the novel. Results have shown how the character has changed in the film adaptation regarding her construction in the film narrative. With the application of intersemiotic translation, it was possible to observe how the analysis of the scenes and subtitles help with the construction and the interpretation of the character.